Philippine oribatid mites of the genus phyllhermannia berlese 1916 (Acari Oribatida: Hermanniidae) - Corpuz-Raros, Leonila A. (2009)
Philippine species of the genus Phyllhermannia Berlese 1916 are taxonomically treated, including six new species, as follows: P. ababa Corpuz-Raros, P canlaonensis Corpuz-Raros, P. longipediseta Corpuz-Raros, P. malindangensis Corpuz-Raros, P. samarensis Corpuz-Raros and P. vermicula Corpuz-Raros. All species are described and illustrated and a key is provided for all 10 species recorded from the country.